Clarification of the confusing identity of Cremanthodium atrocapitatum (Asteraceae, Senecioneae), with a new combination and a new species in the genus - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
Cremanthodium atrocapitatum (Asteraceae, Senecioneae) has been previously largely misunderstood, resulting in considerable taxonomic confusion involving several taxa. Based on observations of both herbarium specimens (including type material) and living plants, here we clarify the taxonomic identity of this species. The Xizang (Tibet) plants previously referred to C. atrocapitatum are described as a new species, i.e. C. bomiense. Cremanthodium campanulatum var. brachytrichum is found to be very close to C. atrocapitatum rather than C. campanulatum, and is thus treated as C. atrocapitatum var. brachytrichum.